Insight into biodiversity of the recently rearranged genus Dickeya - Hugouvieux-Cotte-Pattat, Nicole; Pédron, Jacques; Van Gijsegem, Frédérique (Frontiers in Plant Science, 2023)
The genus Dickeya includes plant pathogenic bacteria attacking a wide range of crops and ornamentals as well as a few environmental isolates from water. Defined on the basis of six species in 2005, this genus now includes 12 recognized species. Despite the description of several new species in recent years, the diversity of the genus Dickeya is not yet fully explored. Many strains have been analyzed for species causing diseases on economically important crops, such as for the potato pathogens D. dianthicola and D. solani. In contrast, only a few strains have been characterized for species of environmental origin or isolated from plants in understudied countries. To gain insights in the Dickeya diversity, recent extensive analyzes were performed on environmental isolates and poorly characterized strains from old collections. Phylogenetic and phenotypic analyzes led to the reclassification of D. paradisiaca (containing strains from tropical or subtropical regions) in the new genus, Musicola, the identification of three water species D. aquatica, D. lacustris and D. undicola, the description of a new species D. poaceaphila including Australian strains isolated from grasses, and the characterization of the new species D. oryzae and D. parazeae, resulting from the subdivision of the species D. zeae. Traits distinguishing each new species were identified from genomic and phenotypic comparisons. The high heterogeneity observed in some species, notably for D. zeae, indicates that additional species still need to be defined. The objective of this study was to clarify the present taxonomy of the genus Dickeya and to reassign the correct species to several Dickeya strains isolated before the current classification.